2023
DOI: 10.1126/sciadv.adg3881
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic effect boosts the production of medium-chain hydrocarbons by fatty acid photodecarboxylase

Abstract: Ongoing climate change is driving the search for renewable and carbon-neutral alternatives to fossil fuels. Photocatalytic conversion of fatty acids to hydrocarbons by fatty acid photodecarboxylase (FAP) represents a promising route to green fuels. However, the alleged low activity of FAP on C2 to C12 fatty acids seemed to preclude the use for synthesis of gasoline-range hydrocarbons. Here, we reveal that Chlorella variabilis FAP ( Cv FAP) can convert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Presently, there are only three known distinct types of natural photoenzymes. Of these, fatty acid photodecarboxylase (FAP) is a flavoenzyme that transforms fatty acids into hydrocarbons and CO 2 with high (70–80 %) photochemical quantum yield (QY) [6–7] . Since its discovery in 2017, [6] FAP has become the subject of intense research, aiming to both unravel its fundamental mechanism [6,8–10] and explore its potential as a template for novel green chemistry photocatalytic reactions [11] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there are only three known distinct types of natural photoenzymes. Of these, fatty acid photodecarboxylase (FAP) is a flavoenzyme that transforms fatty acids into hydrocarbons and CO 2 with high (70–80 %) photochemical quantum yield (QY) [6–7] . Since its discovery in 2017, [6] FAP has become the subject of intense research, aiming to both unravel its fundamental mechanism [6,8–10] and explore its potential as a template for novel green chemistry photocatalytic reactions [11] .…”
Section: Methodsmentioning
confidence: 99%
“…Of these, fatty acid photodecarboxylase (FAP) is a flavoenzyme that transforms fatty acids into hydrocarbons and CO 2 with high (70-80 %) photochemical quantum yield (QY). [6][7] Since its discovery in 2017, [6] FAP has become the subject of intense research, aiming to both unravel its fundamental mechanism [6,[8][9][10] and explore its potential as a template for novel green chemistry photocatalytic reactions. [11] These research lines are intertwined, as understanding the mechanism is essential for the design of derived photocatalysts.…”
mentioning
confidence: 99%
“…As photosynthetic microorganisms, microalgae also harbor a distinctive pathway for alka(e)ne synthesis (9). The discovery of fatty acid photodecarboxylase (FAP) in green microalgae (10) has enriched our repertoire of alka(e)ne-forming enzymes because of the unique photocatalytic process of FAP, which converts free fatty acids (FFA) to alka(e)nes using light in the range 350-530 nm (11,12). FAP belongs to an algal-specific clade of glucose methanol choline (GMC) oxidoreductase family and phylogenetic analysis showed that this photoenzyme is conserved in photosynthesis-retained algal lineages (13).…”
Section: Introductionmentioning
confidence: 99%